THE UNIVERSITY OF CHARCAS: THEORY AND POLITICAL ACTION (2011)
This paper analyzes the leading role he assumed the Universidad San Francisco Xavier de Chuquisaca during debates and political events that spanned the period runs from the expulsion of the Jesuits to the process of selfgovernment. The analysis will focus on those discourses and practices which helped with the training of men of learning and how these are linked with the construction and recreation of elite political and cultural. In addition, we intend to consider the links between political and administrative institutions of the Crown. Since the study of the ways in which these links were established can be glimpsed disputes, conflicts and responsibilities between actors. In terms of methodology, will be used for the understanding of those social action developed by the Interpretative perspectives and political history. These perspectives will realize not only the forms of assistance from the man of learning in the political, institutional and legal, but on a political process that had as protagonists Doctors and lawyers on the revolutionary events of Charcas, Buenos Aires and Quito.